2017
DOI: 10.1007/s13365-017-0529-9
|View full text |Cite
|
Sign up to set email alerts
|

An oral form of methylglyoxal-bis-guanylhydrazone reduces monocyte activation and traffic to the dorsal root ganglia in a primate model of HIV-peripheral neuropathy

Abstract: Peripheral neuropathy (PN) is a major comorbidity of HIV infection that is caused in part by chronic immune activation. HIV-PN is associated with infiltration of monocytes/macrophages to the dorsal root ganglia (DRG) causing neuronal loss and formation of Nageotte nodules. Here, we used an oral form of methylglyoxal-bis-guanylhydrazone (MGBG), a polyamine biosynthesis inhibitor, to specifically reduce activation of myeloid cells. MGBG is selectively taken up by monocyte/macrophages in vitro and inhibits HIV p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Moreover, studies elucidating the role of monocytes/macrophages in SIV pathogenesis have indicated that monocyte/macrophage accumulation correlates with SIV disease severity and progression, tissue damage in the lung and gut, and SIV-associated encephalitis [ 61 63 ]. Importantly, inhibiting macrophage accumulation has shown therapeutic benefits in models of both liver disease and SIV infection [ 36 , 38 , 39 , 64 , 65 ]. In our study, we observed an increase in hepatic monocyte/macrophages during SIV infection that correlated with both inflammatory (TNFα, CCL3) and fibrosis (TGFβ) mediators suggesting multiple, and maybe even opposing, roles during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies elucidating the role of monocytes/macrophages in SIV pathogenesis have indicated that monocyte/macrophage accumulation correlates with SIV disease severity and progression, tissue damage in the lung and gut, and SIV-associated encephalitis [ 61 63 ]. Importantly, inhibiting macrophage accumulation has shown therapeutic benefits in models of both liver disease and SIV infection [ 36 , 38 , 39 , 64 , 65 ]. In our study, we observed an increase in hepatic monocyte/macrophages during SIV infection that correlated with both inflammatory (TNFα, CCL3) and fibrosis (TGFβ) mediators suggesting multiple, and maybe even opposing, roles during infection.…”
Section: Discussionmentioning
confidence: 99%
“…In a simian immunodeficiency virus encephalopathy (SIVE) model wherein OPN expression in brain macrophages contributes to AIDS dementia pathogenesis, MGBG inhibits expression of OPN and SIV p28 expression within the brain, and appears moderately effective in preventing the macaques from developing SIVE [ 71 ]. MGBG also reduces monocyte activation, the dorsal root ganglia pathology, and inflammation in the SIVE model [ 72 ]. In this model, SIV infected macaques also developed myocarditis and early atherosclerosis, processes independent of the presence of infected cells within diseased tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma SIV-RNA was quantified using real-time PCR for all animals used in this study, as previously described. 44 The threshold sensitivity was 15 copy Eq/mL, with an average interassay %CV of <25%.…”
Section: Viral Load Measurementmentioning
confidence: 97%